Evaluation of Different PCR-Based Assays and LAMP Method for Rapid Detection of Phytophthora infestans by Targeting the Ypt1 Gene - Khan, Mehran; Li, Benjin; Jiang, Yue; Weng, Qiyong; Chen, Qinghe (Frontiers in Microbiology, 2017)
Late blight, caused by the oomycete Phytophthora infestans, is one of the most devastating diseases affecting potato and tomato worldwide. Early diagnosis of the P. infestans pathogen causing late blight should be the top priority for addressing disease epidemics and management. In this study, we performed a loop-mediated isothermal amplification (LAMP) assay, conventional polymerase chain reaction (PCR), nested PCR, and real-time PCR to verify and compare the sensitivity and specificity of the reaction based on the Ypt1 (Ras-related protein) gene of P. infestans. In comparison with the PCR-based assays, the LAMP technique led to higher specificity and sensitivity, using uncomplicated equipment with an equivalent time frame. All 43 P. infestans isolates, yielded positive detection results using LAMP assay showing no cross reaction with other Phytophthora spp., oomycetes or fungal pathogens. The LAMP assay yielded the lowest detectable DNA concentration (1.28 × 10–4 ng μL–1), being 10 times more sensitive than nested PCR (1.28 × 10–3 ng μL–1), 100 times more sensitive than real-time PCR (1.28 × 10–2 ng μL–1) and 103 times more sensitive than the conventional PCR assay (1.28 × 10–1 ng μL–1). In the field experiment, the LAMP assay outperformed the other tests by amplifying only diseased tissues (leaf and stem), and showing no positive reaction in healthy tissues. Overall, the LAMP assay developed in this study provides a specific, sensitive, simple, and effective visual method for detection of the P. infestans pathogen, and is therefore suitable for application in early prediction of the disease to reduce the risk of epidemics.